BA : an insider's guide - Jury, Rebecca, 1987- (Auckland University Press, 2012)
Offering 10 steps to obtaining an arts degree at a New Zealand university, this handbook serves as a roadmap for students to discover success in college. From finding the best snacks on campus to realizing your lecturer is a fellow human being, this guide answers the important questions, including What is a bachelor's degree all about? How does one decide which courses to take? and What is a tutorial? Anyone interested achieving work-life balance, improving study habits, conquering essays and exams-all while having fun along the way.